Co 11015 (ATULYA) A RECENTLY NOTIFIED SUGARCANE VARIETY FOR TAMIL NADU - Hemaprabha, G; Appunu, C; Mohanraj, K; Annadurai, A; Alarmelu, S; Sreenivasa, V; Karuppaiyan, R; Shanthi, R M; Govindaraj, P; Mahadevaiah, C; Pathy, T Lakshmi; Mahadevaswamy, H K; et al. (Journal of Sugarcane Research, 2020)
A DESCRIPTION OF Co 11015 (ATULYA) A RECENTLY NOTIFIED SUGARCANE VARIETY FOR TAMIL NADU